Sitaron ki dunya (Pakistan Science Foundation Islamabad, 1998)
"Sitaron Ki Dunya" is a captivating story that takes readers on a journey through the cosmos. It explores the wonders of the universe, from planets and stars to galaxies and black holes. This book sparks curiosity and wonder, encouraging young readers to dream big and explore the limitless possibilities of the universe.